Risk analysis and portfolio modelling - David E. Allen; Elisa Luciano (MDPI, 2019)
Financial Risk Measurement is a challenging task, because both the types of risk and the techniques evolve very quickly. This book collects a number of novel contributions to the measurement of financial risk, which address either non-fully explored risks or risk takers, and does so in a wide variety of empirical contexts.
Keywords: 330